2021
DOI: 10.1080/10095020.2020.1864232
|View full text |Cite|
|
Sign up to set email alerts
|

Spatio-temporal-spectral observation model for urban remote sensing

Abstract: Taking cities as objects being observed, urban remote sensing is an important branch of remote sensing. Given the complexity of the urban scenes, urban remote sensing observation requires data with a high temporal resolution, high spatial resolution, and high spectral resolution. To the best of our knowledge, however, no satellite owns all the above characteristics. Thus, it is necessary to coordinate data from existing remote sensing satellites to meet the needs of urban observation. In this study, we abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 35 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Additionally, novel techniques using deep learning algorithms can utilize the spectral, spatial, and temporal characteristics of multi-source imagery, including optical, SAR, LiDAR, and even street view data. Several studies have shown its successful application to urban areas and crop-type delineation, potentially applicable to mapping the various rice ecosystems (Shao, Wu, and Li 2021;Shao et al 2019;Shao, Zhang, and Wang 2017;Prins and Van Niekerk 2020). Finally, the irrigation infrastructure covered was only NIS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, novel techniques using deep learning algorithms can utilize the spectral, spatial, and temporal characteristics of multi-source imagery, including optical, SAR, LiDAR, and even street view data. Several studies have shown its successful application to urban areas and crop-type delineation, potentially applicable to mapping the various rice ecosystems (Shao, Wu, and Li 2021;Shao et al 2019;Shao, Zhang, and Wang 2017;Prins and Van Niekerk 2020). Finally, the irrigation infrastructure covered was only NIS.…”
Section: Discussionmentioning
confidence: 99%
“…Datasets of broad sizes exist in several real data applications such as pattern recognition, data mining, signal processing, machine learning, text processing, image processing, and web content classification [1][2][3]. These datasets typically contain a significant range of hard-to-cope features.…”
Section: Introductionmentioning
confidence: 99%
“…The LiDAR point cloud data obtained by MMS can be used to draw large-scale topographic maps and electronic maps, power-line inspection and so on. Fusing panoramic image data collected by MMS and LiDAR data, a true color point cloud threedimensional model can be obtained, which can be applied to road target detection, high-precision map making and urban three-dimensional scene display, et al (Shao and Cai 2018;Shao, Zhang, and Wang 2017;Shao et al 2016;Shao, Wu, and Li 2021). It becomes increasingly important since the emergence of some novel techniques, such as autonomous driving, urban brain, digital twin city, et al (Shao et al 2020;Li et al 2013;Shao and Li 2011;Shams et al 2018;Li et al 2016;Craciun et al 2014;Yoshimura et al 2016;Yi and Li 2007;Sester 2020;Yang and Wang 2016;Hollick, Helmholz, and Belton 2016;Ghouaiel and Lefèvre 2016;Sun et al 2016).…”
Section: Introductionmentioning
confidence: 99%